Hedging in different types of discourse - Tatiana I. Gribanova; Tamara M. Gaidukova (Peoples' Friendship University of Russia (RUDN University), 2019)
The article describes discourse features of some of the most common hedges observed in modern English and explores their communicative impact on the utterance. The authors apply Prince et al.'s (1982) classification of hedges into approximators (modify the propositional content conveyed in the utterance) and shields (modify the truth value of the utterance) to analyse hedging behaviour in two discourse genres: the interview and political speeches. The paper aims to identify the most common types of hedges used in the two types of discourse, explore their structural types and pragmatic features, and account for their usage in the two types of discourse. The study is conducted within the framework of contemporary linguistics, such as functional grammar, pragmatics and comparative analysis. The authors make inferences about the nature of hedging, key features of hedges and their discourse-marked specifics.